Medical Record Information System Testing Using User Acceptance Testing to Determine System Quality - Budisaputro, Crismantoro; Anardani, Sri; Riyanto, Slamet; Kusdwiadji, Agustinus (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Software testing is needed to find errors so that it can be ensured that the system works as expected. A software test that is not implemented seriously will have an adverse impact and cause various problems when used by end users. The learning process for STIKES Bhakti Husada Mulia Madiun medical record students includes practicum activities where students practice using the medical record system (SimRS) provided in the laboratory. SimRS was created to fulfill its function as a medium for student practical learning. However, in the process of implementing SimRS it is still unknown whether the system used is in accordance with students' practicum needs or not. Testing in this research uses User Acceptance Testing, namely testing 3 aspects consisting of software engineering test aspects, system functional tests, system visual tests by distributing questionnaires to 30 student respondents. Tabulated results of questionnaire calculations using the approach from Aydin & Tasci. The tabulation results show that for tests related to software engineering (RPL) the average score is 4.36, which means ready to go ahead or ready to continue. For tests related to system functionality, the average score is 4.40, which means ready go ahead or ready to continue. For tests related to the visual system, the average score was 4.35, which means ready to go ahead or ready to continue.